Fidelity vs. Infidelity: An Investigation of the Ideational and Illocutionary Strategies Used in the Two Persian Renderings of Shakespeare's Macbeth - Jamshidian, Elaheh; Dastjerdi, Hossein Vahid (Mediterranean Journal of Social Sciences, 2012)
This study is an attempt to identify and describe certain ideational and illocutionary strategies which translators can make useof in their challenging task of translating literary works. They will be analyzed based on a hybrid framework comprising Halliday'ssystemic functional linguistics (SFL) and Lefevere's illocutionary strategies. To show such strategies at work, two Persian translations ofShakespeare's Macbeth were selected: one by Shadman (1972) and the other by Ashouri (1992). A descriptive and comparativeanalysis of the two translations, with a close eye on the source text, was done on the basis of ideational strategies (i.e. poetic function formeaning) and illocutionary strategies (i.e. archaism and rhyme for form). The findings revealed how the combination of the strategies, ifdone ideationally, could lead to the closest target language approximation of Shakespeare's elegance and balance in creating Macbeth.Thus, the study also tested the hypothesis that the very ideational combination of illocutionary strategies would bring forth a relativereconciliation for the old dichotomy of "fidelity" vs. "beauty" in the realm of literary translation.